Chapter Transmission of useful knowledge in texts written by craftsmen. Two case studies from the Holy Roman Empire - Bruch, Julia (Datini Studies in Economic History, 2023)
In medieval and early modern crafts, useful knowledge was taught in the workshops. There, innovation took place. Craftsmen exchanged knowledge on journeys or through voluntary and forced migration. This system of knowledge transfer does not need writing, although craftsmen used writing both in the workshop and in the administration of the guilds and the towns. However, transmission of knowledge remained oral. This contrasts with countless craftsmen's manuscripts that conveyed technical knowledge about crafts in text and images. This essay argues that these manuals were equally crucial for the transmission of useful knowledge between master craftsmen as well as the sale of products to clients. A book on plate harnesses and one on bell and gun casting are introduced as examples.